Pattern of Sinonasal Tumors in Eastern Nepal - Nepal, A; Joshi, RR; Chettri, ST; Karki, S (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Carcinoma; maxillectomy, papilloma; sinonasal tumor DOI: 10.3126/njenthns.v1i2.4755 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.9-11